Characterization of calcium alginate/ deacetylated konjac glucomannan blend films prepared by Ca2+ crosslinking and deacetylation. (September 2018) - Li, Jiwei; Ma, Jianwei; Chen, Shaojuan; He, Jinmei; Huang, Yudong
Abstract: In this work, calcium alginate (Ca-SA)/deacetylated konjac glucomannan (DKGM) blend films were prepared by Ca 2+ crosslinking of sodium alginate (SA) and deacetylation of konjac glucomannan (KGM). The structure analysis by Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and thermogravimetry (TGA) indicated that there was a strong interaction between Ca-SA and DKGM, which was resulted from the Ca 2+ crosslinking of SA and intermolecular hydrogen bonds caused by the removal of acetyl groups on molecular chains of KGM, i.e. deacetylation of KGM. The obtained property findings revealed that the surface smoothness and transparency of the blended films were decreased with increasing the KGM/DKGM content. Moreover, the deacetylation of KGM decreased the swelling capacity of the blended films, while improved the thermal stability, surface hydrophobicity, and tensile strength of the blended films. In conclusion, this study provided an alternative improvement for the development of polysaccharide based packaging materials. Graphical abstract: Image Highlights: Calcium alginate/deacetylated konjac glucomannan (Ca-SA/DKGM) films were prepared. Water sensitivity of the Ca-SA/DKGM films was reduced. Surface hydrophobicity of the Ca-SA/DKGM films was improved. Tensile properties of the Ca-SA/DKGM films were enhanced.